Durability-related performance of concrete containing fine recycled aggregates from crushed bricks and sanitary ware. (15th January 2016) - Vieira, T.; Alves, A.; de Brito, J.; Correia, J.R.; Silva, R.V.
Abstract: Information on the effects of incorporating fine recycled ceramic aggregates on concrete's durability is very scarce. This paper presents an experimental study using aggregates sourced from crushed red clay ceramic bricks (CBAs) and sanitary ware (SWA). Different concrete mixes were produced where the fine natural aggregate fraction was partially or fully replaced (20%, 50% and 100%, by volume) by each of these materials. Shrinkage, water absorption by immersion, water absorption by capillary action, carbonation and chloride ion penetration tests were carried out. Results show that using fine CBA provides better performance in terms of water absorption by capillarity and chloride ion penetration, contrarily to shrinkage, water absorption by immersion and carbonation penetration. Using fine SWA leads to a similar performance in terms of shrinkage, but all other properties are significantly and detrimentally affected. Notwithstanding the increased water requirement due to the high absorption capacity of CBA and the formation of agglomerated particles with SWA, this paper shows that a judicious use of these materials may allow the production of adequate structural concrete; in mixes with SWA the use of superplasticizers is a very effective approach in preventing the formation of clusters, even providing a better performance than the control concrete. Graphical abstract: Highlights: Concrete produced with fine aggregates from crushed ceramic bricks and sanitary ware Great cohesive forces were found in fine SWAs' vitreous surfaces Concrete with fine CBA exhibited better performance in terms of permeability Specimens with increasing fine CBA content exhibited pozzolanic activity The use of fine SWA leads to a similar performance in terms of shrinkage